Impact of pre‐ablation weight loss on the success of catheter ablation for atrial fibrillation. (5th July 2021) - Peigh, Graham; Wasserlauf, Jeremiah; Vogel, Kelly; Kaplan, Rachel M.; Pfenniger, Anna; Marks, Daniel; Mehta, Arjun; Chicos, Alexandru B.; Arora, Rishi; Kim, Susan; Lin, Albert; Verma, Nishant; et al.
Abstract: Introduction: Obesity is an established risk factor for recurrent atrial fibrillation (AF) after ablation. The impact of pre‐procedure weight changes on freedom from AF (FFAF) after ablation in obese and nonobese patients is unknown. Methods: A single‐center retrospective cohort study of patients undergoing pulmonary vein isolation was performed. Before ablation, all candidates were encouraged to adopt healthy lifestyle habits according to American Heart Association guidelines, including weight loss, by their physician. The primary endpoint was FFAF through 1‐year after completion of the 3‐month blanking period. Results: Of the 601 patients (68% male; average age 62.1 ± 10.3 years) included in analysis, 234 patients (38.9%) were obese (body mass index ≥ 30) and 315 (52.4%) had paroxysmal AF. FFAF was observed in 420 patients (69.9%) at 15 months. Percent change in weight that occurred during the year before ablation independently predicted FFAF through 15‐months in all patients (adjusted odds ratio =  1.17, 95% confidence interval: 1.11–1.23). Subgroup analyses based on paroxysmal vs persistent AF, presence of obesity, and history of prior ablation were performed. Percent change in weight over the year before ablation was independently associated with FFAF in all subgroups except nonobese patients with persistent AF. Conclusion: Pre‐ablation weight loss was associated with FFAF in both obese and nonobese patients. Further studies are needed to define the optimal approach to weight loss before AF ablation.